Alfabetização financeira e ruralidade no município de Capistrano - Ceará - Reis, Maria Vanessa Silva dos (2023)
The recognition of financial literacy as an essential skill for individuals is increasing increasingly in the global financial scenario, becoming a long-term political priority. Considering the increasing complexity of daily financial transactions in the face of increasingly challenging macroeconomic scenarios, the evidence of financial illiteracy not only raises important issues for politics, but also has implications for the financial behavior of individuals living in rural emerging economies, as they are easy targets of information asymmetry. This study has as research locus the rural area of the municipality of Capistrano, in order to analyze the level of financial literacy of the rural environment, since these have significant participation in the local and Brazilian economy. This municipality stands out as the fifth with the largest rural population and the highest Gross Production Value of agricultural establishments in the Massif region of Baturité. Thus, this objective was sought by identifying the socioeconomic and demographic profiles of rural individuals; the analysis of the financial profile and, finally, the measurement of the level of financial literacy. Data collection occurred through direct field research with the application of 175 questionnaires in the municipality under analysis. Cluster analysis and discriminant analysis were applied, with the hypothesis, contained in the international literature, that individuals living in rural areas have a low propensity to integrate the group with a high level of financial literacy. The results showed that the researched have a low level of financial literacy, starting from the formation of three homogeneous groups in the analysis of clusters (low, medium and high level of financial literacy), being confirmed by discriminant analysis. In addition, the hypothesis was confirmed, verifying that the rural population surveyed has a low level of financial literacy, in relation to their attitudes, behaviors and financial knowledge. These results become relevant for the development of strategies or actions focused on the rural environment and their specificities, since financial literacy goes beyond the fact of impacting on the financial health of those who hold it, but also collaborates directly and indirectly in the development of the environment in which they live.